Cobalt-nitrogen-doped graphdiyne as an efficient bifunctional catalyst for oxygen reduction and hydrogen evolution reactions. (June 2019) - Wang, Xin; Yang, Ze; Si, Wenyan; Shen, Xiangyan; Li, Xiaodong; Li, Ru; Lv, Qing; Wang, Ning; Huang, Changshui
Abstract: For replacing the use of rare precious metals, finding an electrocatalyst with low-cost, stable and excellent activity for both the oxygen reduction reactions (ORR) and hydrogen evolution reactions (HER) is desirable and challenging. Herein, a novel electrocatalyst of cobalt (Co) and nitrogen (N) doped graphdiyne (Co-N-GDY) was designed and synthesized using a facile method with just a small amount of Co precursor to reach up to 1.3 wt % based on XPS data. Among them, the 1% Co-N-GDY, synthesized with 1 wt % of Co in the preparation stage, was demonstrated as the most effective ORR and HER catalyst. Due to the synergistic effect of Co, N, GDY and strong interaction between Co and GDY, the Co-N-GDY exhibited excellent ORR and HER catalytic performance. As for ORR, the activity of 1% Co-N-GDY is comparable to that of commercial Pt/C. Especially the half-wave potential of 1% Co-N-GDY is superior to most previously reported Co-based carbon materials. In HER, the 1% Co-N-GDY shows a low onset overpotential of 97 mV and a small Tafel slope of 132 mV per decade, which exhibits comparable or even better performance than many reported non-precious metals catalysts. Graphical abstract: Image 1